A Comparative Study With In Vitro Ultrasonographic and Histologic Grading of Metatarsal Head Cartilage in Rheumatoid Arthritis. (July 2015) - Onodera, Tomohiro; Kasahara, Yasuhiko; Kasemura, Toshiyuki; Suzuki, Yuki; Kondo, Eiji; Iwasaki, Norimasa
Background: Ultrasonography is among the valid methods to assess articular cartilage in the foot. This study aimed to evaluate the validity of ultrasonographic grading to assess metatarsal head articular cartilage for rheumatoid forefoot deformity in vivo and to compare the findings with in vitro ultrasonographic and histologic gradings. Methods: Participants were 15 patients scheduled to undergo resection arthroplasty of the metatarsal heads of the lesser toes because of rheumatoid arthritis of the metatarsophalangeal joints. Ultrasonographic examination was performed in vivo the day before surgery. Specimens of the second to fifth metatarsal heads taken intraoperatively were graded from in vitro ultrasonographic and histologic evaluations. Correlations among in vivo ultrasonographic, in vitro ultrasonographic, and histologic gradings were analyzed. Results: In 46 metatarsal heads, the distribution of grading ranged from grade 1 to 6 for in vivo ultrasonographic examinations and from grade 1 to 4 for histologic examinations. In vivo ultrasonographic grading showed significant correlation to both in vitro ultrasonographic grading ( P < .001, R = 0.74) and histologic grading ( P < .001, R = 0.67). Conclusions: The significant correlations between in vivo ultrasonographic and histologic gradings suggest that a semiquantitative in vivo ultrasonographic assessment of forefoot deformity in rheumatoid arthritis may be possible. Ultrasonographic grading may prove useful for pre- and postoperative evaluation of remaining joint function in rheumatoid forefoot deformity. An ultrasonographic grading system for remaining joint surfaces might be helpful in selecting surgical procedures such as joint-sparing osteotomy and metatarsal head resection. Level of Evidence: Level IV, case series.